2011
DOI: 10.1094/pdis-08-10-0615
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Common Scab of Potato Caused by Streptomyces turgidiscabies Using Lopsided Oat Green Manure

Abstract: Field experiments were conducted to determine the effect of green manure as fallow on common scab of potato caused by Streptomyces turgidiscabies. Significantly fewer diseased tubers were harvested from soil incorporated with lopsided oat or woolly pod vetch compared with those from oat and continuous potato cultivation in a planter experiment. Each field experiment consisted of lopsided oat cultivated during the spring and summer prior to the potato planting. Comparisons were also made with several other trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…One dominant ASV identified for Streptomyces (ASV_001) in the present study shared 100% identity with Streptomyces scabiei and Streptomyces turgidiscabies (Table S5). Consistent with these results, sugar beet has been reported as an alternate host for S. turgidiscabie, and, thus, potato production following sugar beet cultivation may cause an outbreak of potato common scab, as reported by Sakuma et al (2011). Besides Streptomyces, three genera in Actinomycetales (Kribbella, Kutzneria, and Amycolatopsis) were identified as dominant genera (Table 2 and 4).…”
Section: Seasonal Shifts In Lateral Root-associated Bacterial Communi...supporting
confidence: 85%
“…One dominant ASV identified for Streptomyces (ASV_001) in the present study shared 100% identity with Streptomyces scabiei and Streptomyces turgidiscabies (Table S5). Consistent with these results, sugar beet has been reported as an alternate host for S. turgidiscabie, and, thus, potato production following sugar beet cultivation may cause an outbreak of potato common scab, as reported by Sakuma et al (2011). Besides Streptomyces, three genera in Actinomycetales (Kribbella, Kutzneria, and Amycolatopsis) were identified as dominant genera (Table 2 and 4).…”
Section: Seasonal Shifts In Lateral Root-associated Bacterial Communi...supporting
confidence: 85%
“…Similarly, it may reduce soil pH and increase soil acidity in relatively acidic soils. At present, the impact of CC on soil physicochemical properties and nutrient availability is mostly tested in relatively acidic soils, while most studies have reported a reduction in soil pH and an increase in soil acidity under CC of several crops such as black pepper [240], tobacco, [241], tea [242], wheat [243], potato [244], corn [245] and soybean [246], including several other crops. A reduction in soil pH under CC is mostly attributed to the use of nitrogenous fertilizers, tillage intensity, biodegradation of crop residues, and resultantly increased production of organic acids in the soil.…”
Section: Soil Physicochemical Properties and Nutrient Deficienciesmentioning
confidence: 99%
“…Treatment with lopsided oat followed by lopsided oat or wooly pod vetch was signi fi cantly more effective (P < 0.001) in suppressing the disease severity than oat and continuous potato cultivation. An increase in the marketable tuber ratio was also greater in this treatment than for oat and continuous potato cultivation (Sakuma et al 2011 ) .…”
Section: Organic Amendmentsmentioning
confidence: 70%